Development of Flow State Self-Regulation Skills and Coping With Musical Performance Anxiety: Design and Evaluation of an Electronically Implemented Psychological Program - Moral-Bofill, Laura; López de la Llave, Andrés; Pérez-Llantada, Mᵃ Carmen; Holgado-Tello, Francisco Pablo (Frontiers in Psychology, 2022)
Positive Psychology has turned its attention to the study of emotions in a scientific and rigorous way. Particularly, to how emotions influence people’s health, performance, or their overall life satisfaction. Within this trend, Flow theory has established a theoretical framework that helps to promote the Flow experience. Flow state, or optimal experience, is a mental state of high concentration and enjoyment that, due to its characteristics, has been considered desirable for the development of the performing activity of performing musicians. Musicians are a population prone to health problems, both psychological and physical, owing to different stressors of their training and professional activity. One of the most common problems is Musical Performance Anxiety. In this investigation, an electronic intervention program was carried out for the development of psychological self-regulation skills whose main objective was to trigger the Flow response in performing musicians and the coping mechanism for Musical Performance Anxiety. A quasi-experimental design was used with a control group in which pre- and post-measures of Flow State, Musical Performance Anxiety and, also, Social Skills were taken. Sixty-two performing musicians from different music colleges in Spain participated in the program. The results of the study showed an increase in Flow state and, in turn, a decrease in Musical Performance Anxiety levels in the participants who carried out the procedure, but not in the control group. Results are under discussion and future lines of research are proposed.